Cover Picture: Co‐existence of Distinct Supramolecular Assemblies in Solution and in the Solid State (Chem. Eur. J. 10/2017). Issue 10 (9th January 2017) - Reddy, G. N. Manjunatha; Huqi, Aida; Iuga, Dinu; Sakurai, Satoshi; Marsh, Andrew; Davis, Jeffery T.; Masiero, Stefano; Brown, Steven P.
Abstract : NMR analysis reveals that quartet assemblies formed by a guanosine building block in solution can transform into a mixture of quartet (Q) and ribbon (R)‐like assemblies after solvent evaporation. Our results demonstrate that the existence of a stable supramolecular structure in solution or in the solid state may not reflect its stability and integrity in another phase. More information can be found in the Full Paper by S. P. Brown et al. onpage 2315 ff.